Spatial distribution and age structure of population as the limiting factor for (balanced) development of Serbia - Jokić Vesna (Arhitektura i Urbanizam, 2013)
The population (human resources) is the bearer of economic and social development. The demographic development is shaped by natural (birth and death) and by migration components (immigration/emigration); when is presented by changes in the number and structures of the population, it can be stimulating, slowing down or can be a limitation for economic, social and spatial development. Demographic changes in Serbia in the first decade of the 21st century are a continuation of the negative tendencies which began in the last decade of the 20th century, substantially fuelled initiated by political and socioeconomic processes. In the last decade, the changes were more intensive and demographic development was marked by extremely depopulation, weakening of demographic potential and aging population. This has resulted in an increase disparity in the territorial distribution of the population (drastically discharge of rural and undeveloped areas). The aim of this research is to analyze the demographic changes in Serbia in the last intercensal period, spatial distribution and age structure of the population as a factor of development / constraints of balanced development.